Glass Transition Temperature Regulates Mechanical Performance in Nacre‐Mimetic Nanocomposites. Issue 20 (9th September 2020) - Lossada, Francisco; Abbasoglu, Tansu; Jiao, Dejin; Hoenders, Daniel; Walther, Andreas
Abstract: Although research in bioinspired nanocomposites is delivering mechanically superior nanocomposite materials, there remain gaps in understanding some fundamental design principles. This article discusses how the mechanical properties of nacre‐mimetic polymer/nanoclay nanocomposites with nanoconfined polymer layers are controlled by the thermo‐mechanical polymer properties, that is, glass transition temperature, T g, using a series of poly(ethylene glycol methyl ether methacrylate ‐co‐N, N ‐dimethylacrylamide) copolymers with tunable T g from 130 to −55 °C. It is elucidated that both the type of copolymer and the nanoconfined polymer layer thickness control energy dissipation and inelastic deformation at high fractions of reinforcements in such bioinspired nanocomposites. Abstract : The design of the energy‐dissipative and soft polymeric phase inside brick‐and‐mortar nacre‐mimetics controls the thermo‐mechanical behavior of the nanocomposites. Variation of the glass transition temperature, T g, of the polymer by macromolecular design provides an understanding and control of the deformation mechanisms, and enables rational design and toughness engineering for future synthetic bioinspired nanocomposites.